PENGGUNAAN MEDIA KARTU BERGAMBAR DALAM MENINGKATKAN PEMAHAMAN MUFRADAT SISWA KELAS VII DI MTSN 5 SOLOK - Tiara Rahmadani (LUGATUNA: Jurnal Prodi PBA, 2023)
This research is entitled "The Use of Picture Card Media in Improving the Mufradat Understanding of Grade VII Students at MTsN 5 Solok" with the aim of the research to improve students' Arabic learning outcomes and their enthusiasm for learning by using picture card media. The method in this research is Classroom Action Research. The population in this study were all seventh grade students (VII), totaling 110 people. While the samples were students in class VII.2 and VII.4, totaling 55 people consisting of 30 male students and 25 female students. This research was conducted from 13 September to 18 November 2022 at MTsN 5 Solok which is located in Jorong Gadung Nagari Surian, Pantai Cermin District, Solok Regency, West Sumatra Province. Data was collected using a research instrument in the form of a test. Based on the results of this study, it was found that the learning level of class VII students at MTsN 5 Solok continued to increase with the media of picture cards. Judging from the results of student tests that continue to increase from before. In test 1 class VII.2 and VII.4 obtained an average class value of 57.85 and 43.74 and in test 2 the average value increased to 70.71 and 72.59, then in test 3 it increased again and fulfilled the minimum completeness criteria are 83.92 and 85.55. And this shows that the use of picture card media in mufradat learning can improve student learning outcomes and add enthusiasm to learning for class VII students at MTsN 5 Solok. Keywords Media, Picture Cards, Mufradat, learning, Arabic language